EXAMINING EID AL-ADHA IN TERMS OF RELIGION, SCIENCE, GENDER, CHARACTER: ISLAMIC BOARDING SCHOOLS STUDENTS PERSPECTIVE - Prasetyo, Dody Rahayu; Noor, Faiq Makhdum (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The absence of research on Eid al-Adha from the point of view of science, gender, and character, has become interesting for research, so that knowledge for students based on Islamic boarding schools becomes holistic. The purpose of this study is to find out how far the understanding of male students (MS) and female students (FS) based in Islamic boarding schools in Madrasah Aliyah Muwahidun (MAM) related to Religion, Science, Gender, and Character (RSGC). The subjects of this study amounted to 45 MS and 50 FS MAM. Data was collected through an open-ended test containing RSGC questions related to Eid al-Adha. The test results are categorized based on the answers. Students with these answers were sampled, then interviewed in depth. The conclusion in this study is that there are similarities and differences in the arguments of male and female students in understanding Eid al-Adha. In terms of religion, FS has more control over verses related to Eid al-Adha than MS. In terms of science, MS is more logical than FS, but FS is more mastery of related science material. In terms of gender, FS and MS tend to have the same roles as men and women. In terms of character, FS is deeper into the feelings felt by Prophet Ibrahim and Prophet Ismail than MS, but FS and MS agree with the character of "happy to share". Although Eid al-Adha is closely related to religion, students' understanding of linking from other aspects is still weak. Therefore, Eid al-Adha has the potential to be included in the Islamic religious education curriculum in Islamic boarding schools.